2014
DOI: 10.3141/2440-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rain on Traffic Operations on Florida Freeways

Abstract: Although the correlation between traffic variables and weather appears to be intuitive, quantifying the effects that weather, especially rain, has on driver response in travel speeds and traffic demands is needed to evaluate practical aspects of traffic operations. Previous studies have researched driver responses to inclement weather on freeways located in northern regions of the United States and Canada. However, driver familiarity with local weather conditions is a factor that should be considered in determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 6 publications
1
16
1
Order By: Relevance
“…Many studies have focused on the impacts of weather on traffic flow characteristics such as average speed, traffic volume and road capacity [4][5][6][7][8][9][10]. Smith, Byrne, et al [4] investigated the impacts of different levels of rainfall intensity on freeway capacity and operation speed based on historical data.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the impacts of weather on traffic flow characteristics such as average speed, traffic volume and road capacity [4][5][6][7][8][9][10]. Smith, Byrne, et al [4] investigated the impacts of different levels of rainfall intensity on freeway capacity and operation speed based on historical data.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, during early evening hours and afternoon peak hours, significant amounts of reductions ranging from 17-76% are observed. In the study of Sando [2] for the Florida roads, it was observed that the average amount of decrease in speed due to rain event ranged from 1.5 to 3.5 mph for the control section of I-95, and it ranged from 1.8-2.5 mph for the control section of I-295. Hourly traffic volumes were also influenced by wet weather conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their model (see Equation 3), the independent variable Expected Volume Factor (EVF) contribution was significantly higher as compared to snow and cold while estimating the daily traffic volume. Roh et al [10,11,17] also used similar models (see Equations (1) and (2)) and it was found that the EDVF can explain about 78% of classified traffic variation. These studies along with other similar studies as shown in Table 1 fail to explain the relationship between the traffic variation, snowfall and temperature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations